2018
DOI: 10.1186/s12917-018-1412-5
|View full text |Cite
|
Sign up to set email alerts
|

Spatial analysis for bovine viral diarrhea virus and bovine herpesvirus type 1 infections in the state of Paraíba, northeastern Brazil

Abstract: BackgroundBovine Viral Diarrhea Virus (BVDV) and Bovine Herpesvirus type 1 (BoHV-1) cause reproductive problems in cattle and restrictions on international trade in animals worldwide. Both infections were detected in cattle herds in the Paraíba state, Northeastern Brazil, however, the spatial distribution and geographic identification of positive herds for these viruses has never been examined. Therefore, the aim of this study was to describe the spatial pattern of apparent prevalence estimate and to identify … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 41 publications
0
4
0
3
Order By: Relevance
“…It is noteworthy that, despite the climatic conditions of the Sertão being different from the Agreste, which presents favorable abiotic factors for T. gondii, the family farm production in the Sertão, with low technification level of the properties, and without the support of important general sanitary measures for the control of infectious diseases, as quarantine of animals coming from other regions (Clementino et al, 2015) are possible factors that may be generating this risk association. In addition, primary clusters of positive herds for important cattle infectious diseases (such as Bovine Viral Diarrhea Virus, Bovine Herpesvirus type 1 and Vesicular Stomatitis) covering the Sertão region were detected in previous surveys (Bezerra et al, 2018;Fernandes et al, 2018).…”
Section: Discussionmentioning
confidence: 96%
“…It is noteworthy that, despite the climatic conditions of the Sertão being different from the Agreste, which presents favorable abiotic factors for T. gondii, the family farm production in the Sertão, with low technification level of the properties, and without the support of important general sanitary measures for the control of infectious diseases, as quarantine of animals coming from other regions (Clementino et al, 2015) are possible factors that may be generating this risk association. In addition, primary clusters of positive herds for important cattle infectious diseases (such as Bovine Viral Diarrhea Virus, Bovine Herpesvirus type 1 and Vesicular Stomatitis) covering the Sertão region were detected in previous surveys (Bezerra et al, 2018;Fernandes et al, 2018).…”
Section: Discussionmentioning
confidence: 96%
“…Вірус ІРТ займає особливе місце в інфекційній патології великої рогатої худоби, тому що він негативно впливає не тільки на респіраторну, але й на імунну, нервову та репродуктивну системи тварин [6,7]. До того ж, цей вірус окрім значного негативного впливу на здоров'я тварин та їх продуктивність [1], значно впливає на можливості міжнародної торгівлі тваринами у всьому світі, значно їх обмежуючи [8].…”
Section: особливості клінічного прояву інфекційного ринотрахеїту вели...unclassified
“…Antibody enzyme linked immunosorbent assay (ELISA) BVD diagnostic tests on blood or milk samples are used commonly to provide data about BVD exposure, both in individual animals and at a herd level. Previous studies have examined genetic clustering of BVD virus 5 , BVD spatial clusters 6,7 and seroprevalence cohorts among young stock in Scottish suckler herds 8 . These studies indicate that distinct subgroups of BVD infected farms can be identified although little is known about how these subgroups change over time.…”
Section: Introductionmentioning
confidence: 99%